2019
DOI: 10.21451/1984-3143-ar2018-0125
|View full text |Cite
|
Sign up to set email alerts
|

The Sertoli cell: what can we learn from different vertebrate models?

Abstract: Besides having medical applications, comparative studies on reproductive biology are very useful, providing, for instance, essential knowledge for basic, conservation and biotechnological research. In order to maintain the reproductive potential and the survival of all vertebrate species, both sperm and steroid production need to occur inside the testis. From the approximately fifty thousand vertebrate species still alive, very few species are already investigated; however, our knowledge regarding Sertoli cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 121 publications
0
6
0
Order By: Relevance
“…We identified that both β-catenin and ZO-1 displayed conjunctive staining patterns from d 130 onwards, suggesting that the blood-testis barrier can form at 130 days of age in pigs, later than Sertoli cell maturation (d 110). Meanwhile, establishment of the blood-testis barrier in porcine testes at d 130 was accompanied by emergence of various stages of spermatocytes and round spermatids, corroborating that the blood-testis barrier, dividing the seminiferous epithelium into the basal and adluminal compartments in which early (spermatogonia and preleptotene spermatocytes) and late spermatogenic cells (advanced spermatocytes and spermatids) are located respectively [ 4 ], is essential for the normal meiotic progression and continuous sperm production. In future, the functionality or integrity evaluation, such as transmission electron microscopy or intercellular tracers, would provide more information about the time when the blood-testis barrier is actually functional.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We identified that both β-catenin and ZO-1 displayed conjunctive staining patterns from d 130 onwards, suggesting that the blood-testis barrier can form at 130 days of age in pigs, later than Sertoli cell maturation (d 110). Meanwhile, establishment of the blood-testis barrier in porcine testes at d 130 was accompanied by emergence of various stages of spermatocytes and round spermatids, corroborating that the blood-testis barrier, dividing the seminiferous epithelium into the basal and adluminal compartments in which early (spermatogonia and preleptotene spermatocytes) and late spermatogenic cells (advanced spermatocytes and spermatids) are located respectively [ 4 ], is essential for the normal meiotic progression and continuous sperm production. In future, the functionality or integrity evaluation, such as transmission electron microscopy or intercellular tracers, would provide more information about the time when the blood-testis barrier is actually functional.…”
Section: Discussionmentioning
confidence: 88%
“…Sertoli cells are the most important somatic cell type within the microenvironment that support and steer male germ cell development during spermatogenesis [ 2 ], and the number of Sertoli cells per testis is a key determinant of sperm generation. Typically, the Sertoli cell proliferation initiates prenatally and terminates before puberty, albeit highly variable among species [ 3 , 4 ]. When they stop division and become mature, Sertoli cells are capable of supporting the entire spermatogenesis, which is along with the establishment of the blood-testis barrier [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spermatogenesis is mediated by the endocrine and testicular autocrine/paracrine factors, such as FSH, LH, and testosterone in the Leydig and Sertoli cells ( Roper and Chaudhari, 2017 ; Lara et al, 2020 ; Sawaied et al, 2020 ). Other hormones are also involved in regulating spermatogenesis, such as insulin and thyroid hormone ( de Kretser et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis of testicular tissue sections before and after sexual maturity in Qianbei Ma goats revealed that the area and diameter of the seminiferous tubules increased with age, and the number of supporting cells changed only slightly. Some researchers have found that testicular supporting cells usually mature before the primiparous stage and lose their proliferative ability after maturation, after which they are maintained at a dynamic level [23].…”
Section: Discussionmentioning
confidence: 99%